Journeying to the past: time travel and mental time travel, how far apart? - Trakas, Marina (Frontiers in Psychology, 2023)
Spatial models dominated memory research throughout much of the 20th century, but in recent decades, the concept of memory as a form of mental time travel (MTT) to the past has gained prominence. Initially introduced as a metaphor, the MTT perspective shifted the focus from internal memory processes to the subjective conscious experience of remembering. Despite its significant impact on empirical and theoretical memory research, there has been limited discussion regarding the meaning and adequacy of the MTT metaphor in accounting for memory. While previous work has addressed the general limitations of the MTT metaphor in explaining memory (Trakas, 2022), the objective of this article is more focused and modest: to gain a better understanding of what constitutes MTT to the past. To achieve this objective, a detailed analysis of the characteristics of MTT to the past is presented through a comparison with time travel (TT) to the past. Although acknowledging that TT does not refer to an existing physical phenomenon, it is an older concept extensively discussed in the philosophical literature and provides commonly accepted grounds, particularly within orthodox theories of time, that can offer insights into the nature of MTT. Six specific characteristics serve as points of comparison: (1) a destination distinct from the present, (2) the distinction between subjective time and objective time, (3) the subjective experience of the time traveler, (4) their differentiation from the past self, (5) the existence of the past, and (6) its unchangeability. Through this research, a detailed exploration of the phenomenal and metaphysical aspects of MTT to the past is undertaken, shedding light on the distinct features that mental time travel to the past acquires when it occurs within the realm of the mind rather than as a physical phenomenon. By examining these characteristics, a deeper understanding of the nature of mental time travel is achieved, offering insights into how it operates in relation to memory and the past.